Anticancer Effect of a Typhonium flagelliforme L. in Raji Cells Through Telomerase Expression - Endang Purwaningsih; Yulia Suciati; Etty Widayanti (Indonesian Journal of Cancer Chemoprevention, 2017)
Cancer cells have a relatively high telomerase activity compared to normal cells, so the cancer cells have the ability to continue to proliferate and undergo mitosis uncontrolled. Telomerase is an enzyme which responsible for telomere length, a DNA segment that is at the end of eukaryotic cell chromosomes. Telomeres and telomerase play a role in the incidence of carcinogenesis. Natural materials such as taro mice (Typhonium flagelliforme) have potential as anticancer. The purpose of the study was to determine the effects of plant extracts of rat taro on the expression of telomerase in cancer cell Raji. The research method is experimental studies in some form cancerous cell culture cell line, Raji. Used as a control normal cells is Vero cell. The Culture medium used RPMI for Raji cell  and M199 for Vero cell. The study consisted of three groups, control, doses of 1 ½ IC50 and IC50 doses. Expression of telomerase enzyme was measured by the Immunohystochemistry method (IHC). The results showed that the expression of telomerase in cancer cells showed values significantly higher than the normal cells (Vero). Giving mice taro plant extracts (Typhonium flagelliforme) were able to decrease the expression of telomerase significantly in both treatment doses. It was concluded that rodent tuber extract (Typhonium flagelliforme Lodd) can reduce the expression of telomerase in Raji cells, so that the rodent tuber extract (Typhonium flagelliforme Lodd) has potential as an anticancer through the expression of telomerase.Keywords: telomerase, IHC, Typhonium flagelliforme